Introduction manner of sulfate acid for improving the performance of SO42-/CEO2 on selective catalytic reduction of NO by NH3 - 宋忠贤 张秋林 宁平 刘昕 樊洁 黄真真 (Journal of rare earths, 2016)
A series of sulfated CeO2 catalysts were synthesized by impregnation and sol-gel methods and used for selective catalytic reduction （SCR） of NOx by NH3. The results showed that the sulfated CeO2 catalysts prepared by sol-gel method showed excellent catalytic activity at 150-50 ℃, and more than 90% NOx conversion was obtained at 232-450 ℃ with a gas hourly space velocity of 60000 h-1. The catalysts were characterized by X-ray diffraction （XRD）, N2 adsorption, Raman, thermogravimetry （TG）, H2-tem- perature-programmed reduction （H2-TPR） and Py-infrared spectroscopy （Py-IR）. The excellent SCR performance was associated with the surface acidity and the micro-structure. The introduction of sulfate acid into CeO2 could increase the amount of BrOnsted and Lewis acid sites over the catalysts, resulting in the improvement of the low temperature activity. The sulfated CeO2 catalysts prepared by sol-gel method possessed lower crystallization degree, excellent redox property and larger specific surface areas, which were responsible for the superior SCR performance.